Disclosure of Sustainability Reporting on Company Financial Performance - Zulfikar, M.; Wahyudi, Ilham; Wijaya Z, Rico (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Disclosure of sustainability reporting is very important for companies, especially to find out the company's corporate social responsibility (CSR). The purpose of this study is to determine the effect of disclosure of economic, environmental and social indicators on the financial performance of companies1 in the oil, gas & coal sub-sector which are listed on the IDX for the period1 2018-2021. The sampling technique used is purposive sampling. The data analysis technique used is multiple linear regression. The results of the study show that the economic dimension variable has no effect on the company performance. The more fulfillment of the economic performance disclosure index will also not affect the company's financial performance. the environmental dimension has a positive and significant effect on company performance. This indicates that the better the environmental dimension will have a good effect on company performance. This is caused by the disclosure of sustainability reports conveying positive information about matters carried out by entities related to environmental issues. The social dimension has no influence on company performance, because the financial performance of entities/companies whose measurement uses Return On Assets pays more attention to the profit earned by the entity/company rather than the disclosure of social performance itself.